Literary translation, symbolic development and inclusion in South Africa - Maricel Botha (Literator, 2021)
Post-apartheid South African society remains characterised by significant social asymmetries and the need for development. Yet development should encompass not only meeting people’s material needs to ensure survival, but also the attainment of higher social ideals such as solidarity, citizenship and inclusion. Literary translation involving local languages has been posited as one way of attaining such ideals, yet this postulation requires further investigation. The main objective of this article is to investigate the intersections between literary translation and social transformation in South Africa from the perspective of symbolic development, which is accompanied and complemented by a consideration of symbolic exclusion. The focus is firstly on the theoretical connections between literary translation, development and inclusion and secondly on the practical disjunctions between these. The article finds that in theory, there is ground to promote literary translation as a means towards symbolic development because of its ability to equalise language statuses and promote intercultural appreciation. Yet, the highly commodified nature of literature amidst the continuation of socioeconomic inequalities as well as the position of English in literature detract from translation’s ability to foster symbolic development realistically within society at large, at least for the moment. From a theoretical perspective, the utility of incorporating development into translation studies remains significant, however, and translation studies could benefit from further investigation of translational development locally, mainly for its ability to direct research practically towards socially beneficial goals, specifically when combined with exclusion.